2006
DOI: 10.1016/j.physleta.2005.10.077
|View full text |Cite
|
Sign up to set email alerts
|

Return probability: Exponential versus Gaussian decay

Abstract: We analyze, both analytically and numerically, the time-dependence of the return probability in closed systems of interacting particles. Main attention is paid to the interplay between two regimes, one of which is characterized by the Gaussian decay of the return probability, and another one is the well known regime of the exponential decay. Our analytical estimates are confirmed by the numerical data obtained for two models with random interaction. In view of these results, we also briefly discuss the dynamic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 32 publications
(70 reference statements)
4
45
0
Order By: Relevance
“…Moreover, as shown in Ref. [82], the change of the SF to the Gaussian corresponds to the predictions for Wigner BRM. Namely, the transition between the two different shapes, Breit-Wigner and Gaussian, occurs at Γ ∼ σ k , where Γ is the Breit-Wigner width (3.14) and σ 2 k is the variance of the strength function defined by Eq.…”
Section: Standard Model Of Strength Functionssupporting
confidence: 74%
See 2 more Smart Citations
“…Moreover, as shown in Ref. [82], the change of the SF to the Gaussian corresponds to the predictions for Wigner BRM. Namely, the transition between the two different shapes, Breit-Wigner and Gaussian, occurs at Γ ∼ σ k , where Γ is the Breit-Wigner width (3.14) and σ 2 k is the variance of the strength function defined by Eq.…”
Section: Standard Model Of Strength Functionssupporting
confidence: 74%
“…The fit to the exponential dependence (6.9) determines Γ 0 ≈ 0.97 that can be compared with the rough estimate (see details in Ref. [82]), In the intermediate regime between Breit-Wigner and Gaussian, there are two time scales, see Fig. 21, middle panel.…”
Section: Survival Probability: Theoretical Backgroundmentioning
confidence: 63%
See 1 more Smart Citation
“…At an intermediate value, μ = λ = 0.4 (middle panels), the fidelity decays exponentially (after the short-time quadratic behavior) for both quenches. An eventual switch to an exponential decay was expected to occur even in the limit of strong perturbation [13,14,30,32]. However, we have shown that when the initial state fills the energy shell substantially (as in the bottom panels of Fig.…”
Section: Ldos Fidelitymentioning
confidence: 63%
“…Because of this, our studies concentrate on initial states that have energy E n 0 very close to the middle of the spectrum. The Fourier transform of a Gaussian LDOS results in the Gaussian decay of the survival probability, e −ω 2 n 0 t 2 , where ω n 0 is the width of the LDOS [1][2][3][4][5]27]. But when doing the Fourier transform, we should also take into account the unavoidable presence of energy bounds in the spectrum.…”
Section: Spin-1/2 Modelmentioning
confidence: 99%